ANALISIS EFEKTIVITAS PAJAK DAERAH, RETRIBUSI DAERAH DAN LAIN- LAIN PENDAPATAN ASLI DAERAH YANG SAH SERTA KONTRIBUSINYA TERHADAP PENDAPATAN ASLI DAERAH - Manik, Junaidi; Fitri, Meutia (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2023)
This study aims to determine the effectiveness and contribution of local tax, local retribution, and other original local revenue to the original local revenue of Aceh Singkil in 2016-2020. This study used the descriptive qualitative method. The data used in this study are primary and secondary data with data collection techniques using documentation and interview techniques. The result of this study indicate that (1) the effectiveness of local tax revenue in Aceh Singkil in 2016-2020 is less effective (77,63%), (2) the effectiveness of local retribution revenue in Aceh Singkil in 2016-2020 is less effective (71,43%), (3) the effectiveness of other original local revenue in Aceh Singkil in 2016-2020 is effective (90,53%), (4) the contribution of local tax to original local revenue of Aceh Singkil in 2016-2020 is less contribution (14,37%), (5) the contribution of retribution to original local revenue of Aceh Singkil in 2016-2020 is good (41,63%), (6) the contribution of other original local revenue to original local revenue of Aceh Singkil in 2016-2020 is a medium contribution (24,03%).